HARMONI Profile: Examining Levels and Predictors of Student Well-Being in Indonesia - Miryam Wedyaswari; Hery Susanto; Karolina Lamtiur Dalimunthe (Masagi: Jurnal Pendidikan Karakter, 2024)
The HARMONI provides a multicomponent approach to measure Indonesia student well-being adapted from the PROSPER framework. We used the measure to describe the overall well-being and the seven components of HARMONI: outcomes, resilience, relationships, purpose, positivity, strengths, and engagement. A cross-sectional study was conducted with socio-demographic and school characteristics as predictors of student well-being. A total of 1579 students from 511 senior high schools completed an online survey. We found that overall well-being based on the HARMONI profile was positive (M=3.92; SD=0.53), with all components showing a trend of optimal well-being. Student well-being is significantly predicted by gender, school area, and school type but not associated with parent income, parent education, grade level, and student major (R2model 1 = .0299). The effect of gender and school type varies by grade level (R2model 2 = .0342;R2model 3 = .0347). The HARMONI can be used not only for measuring well-being but also as a structure for character education. The findings suggest that designing HARMONI-based character education needs to accommodate gender differences, grade levels, school areas, and school types.